Corrigendum to ?Rainfall-runoff modelling based on global climate model and tropical rainfall measuring mission (GCM -TRMM): A case study in Hulu Terengganu catchment, Malaysia? [Heliyon 9, Issue 5, May 2023, Article e15740] (Heliyon (2023) 9(5), (S240584402302947X), (10.1016/j.heliyon.2023.e15740)) - Zanial W.N.C.W.; Malek M.A.; Md Reba M.N.; Zaini N.; Ahmed A.N.; Sherif M.; Elshafie A. (Elsevier Ltd, 2025)
The authors apologize for any potential confusion caused by the use of the two phrases ?ozone harming substance? and ?least-squares relapse? in the original article. The phrase ?ozone harming substance? was employed to describe the implications of ozone-depleting substances on environment and the phrase ?least-squares relapse? was employed to describe least-squares regression as statistical method used for estimation. To improve the article the authors, correct the phrase ?ozone harming substance? in section 1 to the well-recognized term ?ozone depleting substance? and correct the phrase ?least-squares relapse? in section 2.4 to the well-recognized term ?least-squares regression.? The authors would like to make apologies for any inconvenience caused. ? 2023 The Author(s)